Component Detection and Evaluation Framework (CDEF): A Semantic Annotation Tool. (August 2020) - Jessurun, Nathan; Paradis, Olivia; Roberts, Alexandra; Asadizanjani, Navid
Abstract: Image labeling is the process of manually assigning a class to subregions within an image for machine learning applications. When these subregions are complex shapes, this process is known as semantic segmentation. We propose a new software application, the Component Detection and Evaluation Framework (CDEF), for creating such semantic labels. The benefits of CDEF over existing tools are highlighted, and further improvements are proposed.